Simulation the future of sustainable development: educational environment its provision - Garashchuk, Olena; Kutsenko, Vira (Herald of Economics, 2024)
Introduction. In the conditions of the ongoing Russian armed aggression, Ukraine suffered significant losses – economic, social, ecological, which negatively affected the socio- economic development of the country as a whole and the standard of living of the population in particular. To ensure recovery and further sustainable socio-economic development in the current conditions of the formation of the information society, the knowledge provided by education is of great importance. Therefore, the issue of the development of education as a factor of socio-economic advancement is gaining importance today.Purpose. Researching the ways (models) of further development of the educational environment as a prerequisite for achieving stable functioning of the social, economic and ecological spheres, improving the well-being of the population.Methods. In the process of research, a number of general scientific and special methods of cognition were used, namely: system analysis, systematization, generalization, logical, monographic, comparative, tabular.Results. The problems of transformation of the educational sector of Ukraine in accordance with today’s requirements are studied. among the important points of the specified process is the active implementation of innovative technologies at all levels of educational activity. In this connection, the main functions of the educational sphere are disclosed and an assessment of the trends that have occurred recently in the sphere of education of Ukraine, in particular in secondary and higher education, is provided. The main components that require priority improvement, ensuring the humanization and quality of educational activity in order to fulfill its educational function are highlighted. The importance of this further improvement of resource, primarily financial provision, including for the formation of the necessary educational environment, is emphasized. It is determined that for this it is worth using the best foreign experience. The components of the educational environment are disclosed, the implementation of which is aimed at socio-economic development as a whole, at the successful solution of acute problems existing in the educational sphere, the place and role of the educational function of the educational environment in this process, at the further development and improvement of each component of the latter.Perspectives. Further research should be aimed at improving the strategy for the development of education and the educational environment. The reform of the latter is connected with the change of the educational paradigm of the industry to a person-oriented one, an important indicator of which is the key elements of competence, which will make it possible to ensure a level that meets modern requirements for training personnel - the main driving force of sustainable socio-economic development of society.